An Analysis of the Optimal Provision of Public Infrastructure : A Computational Model Using Mexican Data - Feltenstein, Andrew (IMF Working Papers; Working Paper ;, 1996)
An intertemporal general equilibrium model is used to examine infrastructure effects on the Mexican national income. Production functions are estimated for the major sectors of the economy in which sectoral output depends on inputs of capital and labor, as well as the stocks of the public infrastructure. The analysis indicates that despite high estimated output elasticities with respect to public infrastructure, increased expenditure on infrastructure has rapidly decreasing benefits. Some benefits could be achieved by modest increases in capital expenditures, although at the cost of significantly higher inflation and real interest rates. The increase in real interest rates causes these benefits to be greatly reduced.